Does Debt Management Matter? YES - Kiguel, Miguel A. (World Bank, Washington, DC, 2012)
Debt management can reduce financial vulnerability by limiting liquidity, and rollover risks. This note reviews Argentina's debt management strategy, towards improving the country's credit rating to an investment grade, providing flexibility, liquidity, and opportunity. However, the risks of refinancing can be larger for domestic currency debt, than for foreign currency debt. Lessons from Argentina's experience suggest that volatile flows can be dealt with, through prudential regulation in the banking sector, and overall sound policies in capital markets. Furthermore, avoiding the conversion of private debt into public debt, also helped Argentina overcome the crisis; but perhaps, the biggest challenge is to develop new indicators of financial vulnerability, which should put more weight on stocks of debt, and other financial assets, rather than on flow indicators, such as the current account deficit.